Unravelling the truth and demystifying the Malay civilisation: reading Sulalatus Salatin with new historicism - Abu Bakar, Roslina; Mamat, Siti Fatimah; Chong, Seng Tong; Abd. Rahman, Ahmad Zufrie; Abdul Hamid, Norashikin (Human Resource Management Academic Research Society, 2022)
Historicism, history, and literature are intertwined. However, some scholars believe that Malay historiographical texts are ahistorical texts. This study focuses on the historical aspects found in the Sulalatus Salatin manuscript. The objective of this study is to identify the historical aspects of Sulalatus Salatin and prove the extent of the truth of those historical aspects. To achieve this objective, the methods used are archival analysis, textual analysis and content analysis. The results show that Sulalatus Salalatin is a manuscript that is recognized as a text in the form of history. This study uses the theory of New Historicism introduced by (Greenblatt, 2005; Gallagher & Greenblatt, 2000) in analysing the historical texts. The study concludes that the aspects of historiography found in Malay historiographical texts contain historical truths.